Mesocosm experiment on the impact of invertebrate predation on zooplankton of a tropical lake - Castilho-Noll, Maria Stela Maioli; Arcifa, Marlene Sofia (Springer, 2007)
Invertebrate predation on zooplankton was investigated in mesocosms in the shallow tropical Lake Monte Alegre, Sauo Paulo State, Brazil, in the summer of 1999. Two treatments were applied: one with natural densities of prey and the predators Chaoborus brasiliensis and the water mite Krendowskia sp. (Pr+), and another without predators (Pr-). Three enclosures (volume: 6.6 m(3) of water per enclosure) per treatment were installed in the sediment of the deepest area of the lake (5.0 m). At the beginning, Chaoborus larvae were present in Pr- enclosures, because of technical difficulties in preventing their entrance, but they virtually disappeared in the course of the experiment. Water mites were almost absent in Pr- enclosures. Chaoborus predation negatively influenced the Daphnia gessneri population, but not the populations of the copepods Tropocyclops prasinus and Thermocyclops decipiens and the rotifers Keratella spp. Death rates of Daphnia were generally significantly higher in the Pr+ treatment; Daphnia densities increased after the disappearance of Chaoborus in Pr-. Copepod losses to predation in the experiment may be compensated by higher fecundity, shorter egg development time, and lower pressure on egg-bearing females, resulting in a lower susceptibility to Chaoborus predation. The predation impact of water mite on microcrustaceans and rotifers in the experiment was negligible.
Keywords: Chaoborus predation; Copepods; Daphnia; enclosure; population dynamics